Study of faceted Au nanoparticle capped ZnO nanowires: antireflection, surface enhanced Raman spectroscopy and photoluminescence aspects. (19th January 2015) - Ghosh, A; Juluri, R R; Guha, P; Sathyavathi, R; Dash, Ajit; Jena, B K; Satyam, P V
Abstract: We report a single step g rowth process of faceted Au nanoparticles (NPs) on highly c -axis oriented ZnO nanowires (NWs) and report that a system with a lower antireflection coefficient also showed higher surface enhanced Raman spectroscopy (SERS) enhanced factors. Well-dispersed Au NPs are grown on silicon substrate using a thin film-in-air-annealing method (using 1 nm and 5 nm thick Au films on silicon and subsequent annealing in air at 800 °C) wherein enhanced oxide growth at the Au–Si interface was used to inhibit inter-diffusion to avoid Au–Si alloy formation (Au/SiO x /Si). These substrates are used to grow aligned ZnO NWs using a high temperature (≈900 °C) chemical vapour deposition method. Depending on the size and areal density of initial catalytic Au NPs, the resultant photoluminescence, reflectance characteristics, and effectiveness as SERS substrates of the faceted Au NP capped ZnO NWs coatings are systematically studied. The highly oriented and faceted Au NPs on ZnO NWs have been used as free standing SERS substrates to detect sub-micro molar crystal violet molecules with an analytical enhancement factor (AEF) of ≥10 4 and with high repeatability. The substrate with high-density Au–ZnO heterostructures (5 nm Au case) found to have larger AEF, very low reflectance (≈0.75%) and more green emission.